2017
DOI: 10.3233/jad-161152
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Macrophages and Microglia by Interferon–γ and Lipopolysaccharide Increases Methylglyoxal Production: A New Mechanism in the Development of Vascular Complications and Cognitive Decline in Type 2 Diabetes Mellitus?

Abstract: Methylglyoxal (MGO), a dicarbonyl compound derived from glucose, is elevated in diabetes mellitus and contributes to vascular complications by crosslinking collagen and increasing arterial stiffness. It is known that MGO contributes to inflammation as it forms advanced glycation end products (AGEs), which activate macrophages via the receptor RAGE. The aim of study was to investigate whether inflammatory activation can increase MGO levels, thereby completing a vicious cycle. In order to validate this, macropha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 169 publications
1
14
0
Order By: Relevance
“…The activation of the methylglyoxal pathway and production of this metabolite has been associated with the induction of a proinflammatory phenotype in macrophages [ 86 ]. In addition, activation of macrophages and microglia with a combination of LPS and IFN-γ reportedly leads to the production and secretion of methylglyoxal [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the methylglyoxal pathway and production of this metabolite has been associated with the induction of a proinflammatory phenotype in macrophages [ 86 ]. In addition, activation of macrophages and microglia with a combination of LPS and IFN-γ reportedly leads to the production and secretion of methylglyoxal [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monocytes/macrophages play an important role in the occurrence and development of T2DM, which is regarded as a type of low-grade inflammation (4,5,30,31). The in vitro results of our previous study using RAW264.7 macrophages revealed that uc.48+ siRNA is able to regulate immune and inflammatory responses, thus influencing the course and outcome of these effects, which are mediated by the P2X 7 receptor (13).…”
Section: Discussionmentioning
confidence: 99%
“…One example of this phenomenon is through increased activation of the first enzyme of the glycolytic pathway, hexokinase. 50 LPS also activates the transcription factor hypoxia-inducible factor 1 alpha (HIF-1 ), 49 46 A prerequisite of protein nitrotyrosination is the interaction of proteins with nitrating agents such as peroxynitrite. 72 Peroxynitrite forms in the presence of the ROS, superoxide (O 2 − ), and the reactive nitrogen species, Nitric Oxide, 73 all induced in M1 macrophages.…”
Section: Discussionmentioning
confidence: 99%